Dinoflagellate cysts as proxies of environmental, ocean and climate changes in the Atlantic realm during the quaternary - Marret, Fabienne; de Vernal, Anne (Frontiers in Ecology and Evolution, 2024)
Over the last four decades, organic-walled dinoflagellate cysts have shown high potential as tracers of past sea-surface conditions during the Quaternary. These microfossils relate to the pelagic productivity of both phototrophic and heterotrophic protist organisms and are recovered in high numbers in almost all marine environment settings from the nearshore and estuarine systems to the distal continental margin. In polar environments, where other conventional proxies are rare or absent, dinoflagellate cysts showed a relatively high diversity of species and a close relationship with sea-ice cover duration, winter and summer temperature, and salinity, enabling quantitative reconstructions of several oceanic variables over time. From the temperate to the tropical latitudes of the Atlantic Ocean, their modern distribution highlights a response to primary productivity and seasonal contrasts in surface temperature. They also have proven that they could be used as tracers of eutrophication in stratified systems and can also highlight human impact on their distribution. In this paper, we present an overview of dinoflagellate cysts as ecological tracers in recent and past sediments of the Atlantic Ocean, from the Arctic to the Antarctic. We provide examples of their use as proxies in paleoclimatic-palaeoceanographic studies at glacial to interglacial time scales, with emphasis on the last ice age to recent (last 25 kyr), the northern North Atlantic and western-eastern tropic North Atlantic. We also discuss their potential as tracers of anthropogenic stress in coastal environments.